PEMAHAMAN ISLAMIC ENTREPRENEURSHIP VALUES SEBAGAI MOTIVASI MEMBANGKITKAN USAHA PASCA PANDEMI COVID-19: (OVERVIEW SURAT QURAISY) - Nur Majdina Dina; Engga Jalaludin (STAI Asy-Syukriyyah, 2023)
Understanding Islamic entrepreneurship is very important to build a community entrepreneurial spirit that is oriented towards worldly and spiritual benefits. Then Islamic principles should be realized, so that entrepreneurship becomes an interesting topic of study that can minimize life's problems, especially economic problems. Through a study with a qualitative approach, this study aims to describe understanding of Islamic entrepreneurship as an attempt to arouse the spirit of entrepreneurship, especially after the Covid-19 pandemic through an overview of the surat Quraisy. The method used in this research is library research or literature review, which collects data from the literature and other sources that support and are related to the discussion in this study. The results of the discussion in this study entrepreneurship is an ideal alternative to the economic crisis, especially after the Covid-19 pandemic, where many businesses have experienced a decline. Islam makes entrepreneurship part of worship, therefore it is important to understand Islamic entrepreneurship in a Muslim so that it is able to bring prosperity to the poor and is worth blessing according to the directions in the surat Quraisy. This research is limited to a qualitative approach through literature review which can be redeveloped with another approach using data analysis methods in case studies, considering the many contemporary economic cases that can be used as research material.